Mišično-skeletne poškodbe pri igralcih golfa s poudarkom na mehanizmih nastanka - Opara, Manca (Šport (Ljubljana), 2023)
In this article, we summarize the scientific literature on musculoskeletal injuries in golfers. Injuries to the lumbar spine and upper limbs are the most common, including: Tendinopathy of the extensor or flexor carpi ulnaris, hook fracture, rupture of the triangular fibro-cartilage complex, DeQuervain syndrome, intersection syndrome, epicondylitis of the elbow, posterior shoulder instability, shoulder impingement syndrome, her- niated disk, vertebral stress fractures, spondylolisthesis, and facet joint arthropathy. The major risk factors are: high volume of exercise, fatigue, inadequate warm-up, inadequate flexibility or muscle strength, and technical errors in the swing. Injuries to the wrist, hand, and elbow are pri- marily caused by the club penetrating the ground before contact with the ball, repetitive motion of the wrist, or an overly strong grip of the club. Shoulder joint injuries can be the result of inadequate rotation of the thoracic spine, which causes the shoulder joint to compensate for the lack of mobility or compression loads that occurs during a particular phase of the swing. Spinal injuries are caused by high compressive, torsional, bending and shear forces on the spine during the swing. Injury prevention measures include adjusting the length, thickness, and weight of the club; adjusting swing technique; proper warm-up; and preventive training. Rehabilitation of golfers should be a multidisciplinary program that includes a physiatrist, physiotherapist and recording of the player’s technique.
Keywords: dejavniki tveganja; golf; poškodbe; preventiva; šport